Healthcarepreneurship Training on Making Antibacterial Liquid Soap (Hand Soap) Made From Hibiscus rosa sinensis L. Extracts - Antari, Arlita Leniseptaria; Saraswati, Indah; Annisaa, Eva; Utomo, Astika Widy; Ekawati, Nuraini; Kurniasari, Teny (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2024)
Healthcare is one of the critical elements of infection prevention and control, one of which can be done by maintaining hand hygiene. Hand washing with soap and flowing water has long been considered a parameter of personal hygiene and is a simple way to reduce the transmission of infections, especially those caused by hand contact between individuals. However, it must still be done by paying attention to the time and the correct way to wash hands according to WHO standards. At this time, various hand soap products have emerged but are not antibacterial. Antibacterial ingredients used as soap base should not contain various kinds of chemicals that are harmful to the health of its users. Therefore, the use of natural ingredients can be an alternative to substitute chemical active substances. One that has been tested for its antibacterial properties is hibiscus flower (Hibiscus rosa sinensis L.). This activity began with presenting the results of the screening on hand washing habits carried out 2 weeks earlier. The next activity is the introduction to making antibacterial hand soap made from hibiscus extract through material presentation and empirical evidence of the potential of hibiscus as an antibacterial, as well as videos about the importance of maintaining hand hygiene through proper hand washing regularly. The activity is expected to make the healthcare UMKM know and understand that hibiscus flowers, which are widely available around their residence, can be used as raw material for making hand soap that has been produced so far, so as to minimize the use of chemical-based antibacterials. The hand soap product produced later became a collaborative product produced by the community, and then registered a patent with the number S00202120213 on November 17th, 2021.